A Review of Hylocereus Production in the United States (Journal of the Professional Association for Cactus Development, 2020)
Pitaya, pitahaya or dragon fruit, grow on a veining epiphytic cactus (Hylocereus sp.) native to the tropical forest regions of Mexico and Central and South America (Mizrahi et al., 1997). The plants grow up tree trunks and are anchored by aerial roots. The fruits have red or pink thornless skins, while the juicy flesh can range from white to magenta. The skin is covered with bracts or "scales", hence the name dragon fruit. The seeds are small and are consumed with the fruit. The fruit can weigh up to 900 grams, but the average weight is between 350 and 450 grams. The weight depends on pollination as well as the variety selection. When ripe, the dragon fruit are most often consumed fresh. In some parts of South America, the pulp is used in drinks.